Case Report on Diabetic Amyotrophy - Sivanandy, Palanisamy; James, Rasna (Indian Journal of Pharmacy Practice)
Diabetic amyotrophy is a rare complication associated with early-stage diabetes. The main symptoms are muscle weakness and pain, usually in the hips and thighs, leading to difficulty in standing and walking. It usually occurs in patients over 60 years of age and hence its morbidity is increased. However, diabetic amyotrophy (DA) is one complication which seems always to respond to better glycaemic control and if this can be achieved the prognosis is good. Here we report a case on non-insulin-dependent diabetes mellitus, who developed diabetic amyotrophy.
Keywords: Diabetes; Insulin; Amyotrophy; Neuropathy; Muscles